Transenamel and transdentinal cytotoxicity of carbamide peroxide bleaching gels on odontoblast-like MDPC-23 cells - Soares, D. G. S. [UNESP]; Ribeiro, A. P. D. [UNESP]; Sacono, N. T. [UNESP]; Coldebella, C. R. [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, C. A. [UNESP] (Wiley-Blackwell, 2011)
P>AimTo evaluate the transenamel and transdentinal cytotoxicity of bleaching gels based on carbamide peroxide (CP) on odontoblast-like cells after different contact times of the products with enamel.MethodologyEnamel/dentine discs were obtained from bovine incisors and placed in artificial pulp chambers. Bleaching gels containing 10% or 16% CP were applied for 8 h day-1 on the enamel side of the discs during periods of 1, 7 or 14 days. Deionized water and artificial saliva served as controls. The extracts (culture medium plus bleaching gel products that diffused through the discs) were collected and applied on previously cultured MDPC-23 cells for 1 h. Cell metabolism was evaluated by the MTT assay, and the data were analysed statistically by one-way anova and Tukey's test (alpha = 0.05). Cell morphology was analysed by SEM.ResultsThere was no significant difference (P > 0.05) between the controls and the groups bleached with 10% CP gel. In the groups bleached with 16% CP gel, however, cell metabolism decreased significantly (P < 0.05) by 40.32%, 30.16% and 26.61% at 1, 7 and 14 days, respectively. There was no significant difference (P > 0.05) between 1, 7 or 14 applications of the gels for either of the CP concentrations.ConclusionRegardless of the number of applications on an enamel surface, the 10% CP bleaching gel did not cause transenamel and transdentinal cytotoxicity to the MDPC-23 cell cultures. However, diffusion of products from the 16% CP gel through enamel and dentine and cytopathic effects to the pulp cells occurred even after a single application of this product on enamel.
Keywords: carbamide peroxide; cytotoxicity; odontoblasts; tooth bleaching